2008
DOI: 10.1007/s12080-008-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Floquet theory: a useful tool for understanding nonequilibrium dynamics

Abstract: Many ecological systems experience periodic variability. Theoretical investigation of population and community dynamics in periodic environments has been hampered by the lack of mathematical tools relative to equilibrium systems. Here, I describe one such mathematical tool that has been rarely used in the ecological literature but has widespread use: Floquet theory. Floquet theory is the study of the stability of linear periodic systems in continuous time. Floquet exponents/multipliers are analogous to the eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 34 publications
0
92
0
Order By: Relevance
“…Stochastic simulations showed that noise can extend the Hopf bifurcation point in both single-(F 31 ) and dual-feedback systems (F 31,32 ), producing oscillations at parameter values that does not lead to oscillations in a deterministic setting. Comparing the bifurcation points in F 31 and F 31,32 at different levels of the inner loop showed that the points were not altered, suggesting that addition of the second loop in the nested arrangement had no effect on the stochastic bifurcation points. Further understanding concerning the interplay between noise and oscillations in coupled-feedback settings should be among the focuses of future systems biology studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stochastic simulations showed that noise can extend the Hopf bifurcation point in both single-(F 31 ) and dual-feedback systems (F 31,32 ), producing oscillations at parameter values that does not lead to oscillations in a deterministic setting. Comparing the bifurcation points in F 31 and F 31,32 at different levels of the inner loop showed that the points were not altered, suggesting that addition of the second loop in the nested arrangement had no effect on the stochastic bifurcation points. Further understanding concerning the interplay between noise and oscillations in coupled-feedback settings should be among the focuses of future systems biology studies.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate analytical treatment, we instead employ the Routh -Hurwitz theorem [29,30] which states that the eigenvalues, essentially the roots of the characteristic polynomial jJ 2 lIj 31,21 . To verify that (2.4) also constitute the sufficient condition for oscillations in these systems, we employed analysis based on the Floquet theory that globally assesses the stability of the obtained periodic solutions [31][32][33]. The mathematical and computational background of the Floquet analysis is given in the electronic supplementary material.…”
Section: ð2:3þmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the forcing electric terms are periodic in time and our system is linear, we may use techniques derived from the Floquet theorem to compute the growth rate s of any perturbation. We will briefly outline these techniques here, mostly following Klausmeier [50] (see also [36,39,51]). …”
Section: Growth Rate: Floquet Analysismentioning
confidence: 99%
“…Even under large perturbations the system always returns to the original periodic orbit after a finite time interval, thus the global stability of the oscillation is very strong. We can distinguish the locally unstable but globally attractive oscillation from the large-amplitude oscillation by calculating the largest Lyapunov exponent of the oscillation [17]. The dashed curve LM indicates the boundary between the orange-triangle and the yellow-pentagon regions for N = 20 and r = 0.4.…”
Section: F Case Of Locally Unstable But Globally Attractive Oscillatmentioning
confidence: 99%